Optimi,zation of concentrations of DMSO and PROH for vitrification of in vitro produced pronucleate buffalo embryos - KUMAR, SURESH; SAXENA, M S; MAURYA, S N (The Indian Journal of Animal Reproduction, 2007)
Good quality cumulus oocyte complex (COCs) aspirated from follicles of >2 mm diameter fromslaughtered buffalo ovaries. The COCs were washed five times in TL-Hepes and cultured in TCM- , 199 containng I 0% FCS, hormones, and antibiotics. The culture was done at 5%CO2 concentration, 95% humidity at a temperature of38.5°C for 26h. In vitro sperm capacitation was achieved using 90 min incubation with heparin (100 mg/ml). In vitro matured oocytes and capacitated spermatozoa were incubated for 20h in pre-equilibrated fertilization drops. The fertilization rates were ascertainedby pronucleus formation. The pronuclus stage embryos were exposed to different mole concentrations(0-4 M) of dimethyl sulphoxide (DMSO) (n = 5 to 24 for each concentration)or 1, 2- propanediol(PROH) or the combination ofDMSO and PROH in serially ascending concentrations grouped at 0.5M interval along with 0.25 M sucrose with 2 minutes equilibration at each step. The embryos werevitrified and stored in liquid nitrogen for 7 or more days and then thawed. Cryoprotectants wereremoved by placement of embryos in medium with serially descending concentrations of thecryoprotectants containing 0.5 M sucrose. The embryos were co-cultured with oviductal cells in TCM-199. The post vitrification cleaving ability was used for assessing suitability of the concentration ofcryoprotectants. The results indicated that 1.5M DMSO provided best cryoprotection (35.71%) topronucleate buffalo embryos followed by 2.0 M (33.33 %) and 2.5 M (33.33 %) PROH. Addition ofPROH and DMSO did not improve embryo survival rate over with that achieved either of these alone.
Keywords: Vitrification; Pronuclus; Buffalo; Embryos